Intellectual Property Rights and Innovation: Evidence from the Human Genome - Williams, Heidi L. (Journal of Political Economy, 2013)
Do intellectual property (IP) rights on existing technologies hinder subsequent innovation? Using newly-collected data on the sequencing of the human genome by the public Human Genome Project and the private firm Celera, this paper estimates the impact of Celera's gene-level IP on subsequent scientific research and product development. Genes initially sequenced by Celera were held with IP for up to two years, but moved into the public domain once re-sequenced by the public effort. Across a range of empirical specifications, I find evidence that Celera's IP led to reductions in subsequent scientific research and product development on the order of 20 to 30 percent. Taken together, these results suggest that Celera's short-term IP had persistent negative effects on subsequent innovation relative to a counterfactual of Celera genes having always been in the public domain.